1994
DOI: 10.1128/aem.60.2.715-721.1994
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Activities of Antibiotics Produced during Infection of the Insect Galleria mellonella by Two Isolates of Xenorhabdus nematophilus

Abstract: Xenorhabdus nematophilus subsp. dutki, an entomopathogenic bacterium, is vectored by steinernematid nematodes into insects, where it produces broad-spectrum antibiotics. The use of the nematode-bacterium complex against soil-dwelling pest insects could introduce antibiotics into the soil via the dead insect fragments during the emergence phase of the nematodes. Studies on the stability and activities of these antibiotics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 21 publications
4
27
0
3
Order By: Relevance
“…In this context, the formulation of both tryptone soya broth and BYP broth include complex organic nitrogen sources and sodium chloride. Our data also verified the previous reports by Maxwell et al [19] and Ji et al [20] regarding the high productivity of fermentation media that contain complex organic nitrogen sources. Chen [21] suggested that the use of different media may change the levels of the expressed antibiotic activity.…”
Section: Effect Of Growth Mediumsupporting
confidence: 93%
“…In this context, the formulation of both tryptone soya broth and BYP broth include complex organic nitrogen sources and sodium chloride. Our data also verified the previous reports by Maxwell et al [19] and Ji et al [20] regarding the high productivity of fermentation media that contain complex organic nitrogen sources. Chen [21] suggested that the use of different media may change the levels of the expressed antibiotic activity.…”
Section: Effect Of Growth Mediumsupporting
confidence: 93%
“…Xcn1 and Xcn2 ( Fig. 1A) are major antibiotics produced by X. nematophila in broth culture (McInerney et al, 1991) and in insects (Maxwell et al, 1994). The NRPS gene, xcnA, previously designated nrps1, was shown to be highly expressed in an ompR strain that displayed a high level of antibiotic activity (Park and Forst, 2006).…”
Section: Identification Of Genes Involved In Xenocoumacin Productionmentioning
confidence: 98%
“…Mutants were analysed for motility as described by Vivas and Goodrich-Blair (2001). Plate assays were performed to observe protease activity (Boemare et al, 1997), lipase activity (Sierra, 1956) and antibiotic activity (Maxwell et al, 1994;Vivas and Goodrich-Blair, 2001). Haemolytic activity was assayed using blood agar plates (Rowe and Welch, 1994) with 5% defibrinated sheep blood (Colorado Serum).…”
Section: Phenotypic Assays For Colonization Mutantsmentioning
confidence: 99%